1994
DOI: 10.1177/019372394018003004
|View full text |Cite
|
Sign up to set email alerts
|

Gender Bias and the 1992 Summer Olympic Games: An Analysis of Television Coverage

Abstract: This study provides a quantitative and qualitative analysis of NBC's coverage of sports that held competitions for both women and men during the 1992 Olympic Games. The study presents results of the broadcast time devoted to women's and men's basketball, volleyball, gymnastics, swimming/diving, track and field, and other sports. The analysis examines qualitative differences in portrayals of female and male athletes. The analysis of each sport evaluated announcers' use of strength and weakness descriptors to ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 7 publications
3
31
2
Order By: Relevance
“…Rather, women's events were presented in such a way that no systematic discrimination between the men's and women's coverage was discernible. This finding is in distinct contrast to previous studies (Duncan et al, 1990;Higgs & Weiller, 1994), which have suggested that coverage of women's team sports have traditionally been trivialized.…”
Section: Narrativescontrasting
confidence: 99%
See 3 more Smart Citations
“…Rather, women's events were presented in such a way that no systematic discrimination between the men's and women's coverage was discernible. This finding is in distinct contrast to previous studies (Duncan et al, 1990;Higgs & Weiller, 1994), which have suggested that coverage of women's team sports have traditionally been trivialized.…”
Section: Narrativescontrasting
confidence: 99%
“…Emphasizing these differences reinforces messages that amplify male hegemony not only in sport but in other realms of life (Lambo & Tucker, 1990). In comparison with the 1992 Olympic Games (Higgs & Weiller, 1994), findings of the present study suggest the following:…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Most previous studies into coverage of female sport have tended to focus on the national or transnational level, either looking at particular sports or large events like the Olympics (Higgs and Weiller 1994;Billings and Eastman 2002;Capranica et al 2005). The general conclusion of the majority of these papers is that there is a large imbalance in the coverage of male and female sports, both in terms of the amount of space they receive in the media, and the way they are portrayed (Bryant 1980;Jones et al 1999).…”
Section: Previous Studiesmentioning
confidence: 99%